Informed consent in scientific research: what should we know? - José Moreira; Susana Miguel; Ana Frade (Cadernos de Saúde)
Informed consent is a pillar of the research and imperative in an ethical dimension. Given its inherent principles in an increasingly rigorous and responsible investigation, this process is complex, making it challenging to reflect on its validity from an ethical and deontological perspective. We are witnessing the fast development of knowledge in biomedicine intrinsic to unprecedented technological innovation, with increased complex studies and repercussions on consent. Among them, the simplification and validation of information to be transmitted to the participant, the possibility to extend the period for clarifying possible doubts, the use of support tools, and optimization of the communication by researchers. Overly technical terms, difficult interpretation of the information, little explanation, different cultures, and sociopolitical ideologies affect the researchers’ differentiation. Given the several legal dimensions of consent, the relevance of free and informed exercise of the rights provided by law for scientific development in health was demonstrated. In addition to an opportunity for effective communication, informed consent must be based on a trust relationship between the investigator and the participant, based on ethical principles. These are essential to the development of rational and robust research, somehow guiding the work to be carried out by researchers, including the principles of beneficence, non-maleficence, justice, autonomy, and precaution. Therefore, the participant assumes an active role in the success or suspension of the investigation, and the investigators are responsible for respecting the informed and free decision.